The 2019 coronavirus (SARS-CoV-2) surface protein (Spike) S1 Receptor Binding Domain undergoes conformational change upon heparin binding - Mycroft-West, Courtney J; Su, Dunhao; Elli, Stefano; Li, Yong; Guimond, Scott E; Miller, Gavin J; Turnbull, Jeremy E; Yates, Edwin A; Guerrini, Marco; Fernig, David G; Andrade De Lima, Marcelo; Skidmore, Mark A (bioRxiv, 2020)
Many pathogens take advantage of the dependence of the host on the interaction of hundreds of extracellular proteins with the glycosaminoglycans heparan sulphate to regulate homeostasis and use heparan sulphate as a means to adhere and gain access to cells. Moreover, mucosal epithelia such as that of the respiratory tract are protected by a layer of mucin polysaccharides, which are usually sulphated. Consequently, the polydisperse, natural products of heparan sulphate and the allied polysaccharide, heparin have been found to be involved and prevent infection by a range of viruses including S-associated coronavirus strain HSR1. Here we use surface plasmon resonance and circular dichroism to measure the interaction between the SARS-CoV- 2 Spike S1 protein receptor binding domain (SARS-CoV-2 S1 RBD) and heparin. The data demonstrate an interaction between the recombinant surface receptor binding domain and the polysaccharide. This has implications for the rapid development of a first-line therapeutic by repurposing heparin and for next-generation, tailor-made, GAG-based antivirals. Competing Interest Statement The authors have declared no competing interest.